High but stable incidence of adult-onset asthma in northern Sweden over the last decades. Issue 3 (5th July 2021) - Räisänen, Petri; Backman, Helena; Hedman, Linnea; Andersson, Martin; Stridsman, Caroline; Kankaanranta, Hannu; Ilmarinen, Pinja; Andersen, Heidi; Piirilä, Päivi; Lindberg, Anne; Lundbäck, Bo; Rönmark, Eva
Background: The prevalence of asthma has increased both among children and adults during the latter half of the 20th century. The prevalence among adults is affected by the incidence of asthma not only in childhood but also in adulthood. Time trends in asthma incidence have been poorly studied. Aims: The aim of this study was to review the incidence of adult-onset asthma from 1996 to 2006 and 2006 to 2016 and compare the risk factor patterns. Methods: In the Obstructive Lung Disease in Northern Sweden (OLIN) studies, two randomly selected population-based samples in the 20–69-year age group participated in postal questionnaire surveys about asthma in 1996 (n=7104, 85%) and 2006 (n=6165, 77%). A 10-year follow-up of the two cohorts with the same validated questionnaire was performed, and 5709 and 4552 responded, respectively. Different definitions of population at risk were used in the calculations of asthma incidence. The protocol followed a study performed between 1986 and 1996 in the same area. Results: The crude incidence rate of physician-diagnosed asthma was 4.4 per 1000 person-years (men 3.8, women 5.5) from 1996 to 2006, and 4.8 per 1000 person-years (men 3.7, women 6.2) from 2006 to 2016. When correcting for possible under-diagnosis at study entry, the incidence rate was 2.4 per 1000 person-years from 1996 to 2006 and 2.6 per 1000 person-years from 2006 to 2016. The incidence rates were similar across age groups. Allergic rhino-conjunctivitis was the main risk factor for incident asthma in both observation periods (risk ratio 2.4–2.6). Conclusions: The incidence of adult-onset asthma has been stable over the last two decades and has remained at a similar level since the 1980s. The high incidence contributes to the increase in asthma prevalence. The incidence of adult-onset asthma in adults has been stable in Sweden over the last 30 years but the relatively high incidence rate in combination with low remission rate in adulthood contributes to the reported increase in asthma prevalence among adults https://bit.ly/2QP0AF4